Sudden illness while driving a vehicle - a retrospective analysis of commercial drivers in Japan - Masahito Hitosugi; Sayaka Gomei; Takao Okubo; Shogo Tokudome (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVE: We performed a retrospective analysis of commercial drivers to clarify the background of incidents of sudden illness while driving. METHODS: The analysis used reports submitted by employers to the Japan Ministry of Land, Infrastructure, Transport, and Tourism regarding commercial drivers who had been ordered to stop driving owing to health problems. RESULTS: Of 211 cases with an average work history of 15.2 years, there were 88 bus drivers, 70 taxi drivers, and 53 truck drivers, 36.0% of who had died as a result of their disease. Among taxi and truck drivers, more than 70% of incidents were due to cardiac, aortic, and cerebrovascular disease. More than 80% of these were unable to avoid traffic accidents caused by sudden illness. However, among bus drivers, cardiac, aortic, and cerebrovascular disease accounted for only 23.5% of incidents, and accidents were avoided in more than half of the cases. The duration between starting work and the incident time was significantly shorter among bus drivers [mean 3.3 hours, standard deviation (SD) 3.1] than taxi (7.7 hours, SD 5.8) and truck (7.2 hours, SD 6.3) drivers (P<0.01). CONCLUSIONS: The difference between the sudden illness rates of taxi and truck drivers and those of bus drivers is due to both reporting bias and differences in the awareness needed to prevent disabling events while driving. As a precaution, physicians should advise commercial drivers to stop driving as soon as they detect slight discomfort. To prevent accidents, more assertive health promotion aimed at professional drivers is needed.